ГЕНЕТИЧЕСКИЕ ОСНОВЫ СИСТЕМАТИКИ ПШЕНИЦ В РОДЕ Triticum L. (Experimental biology, 2015)
The genetics of specific traits of wheat is analysed. Taxonomic traits by K.Linneey are based on the minor genes and аre controlled by very simple gene (1-3 and polymeric) relation. These simple gene relations can't be sufficient criterion for definition of the specific status. From a point allopolyploidy evolution and alteration of fragility of an ear of wild species are the basic systems of formation of species. Wild tetraploid wheat – Emmer has arisen by this way. So, together with a result of long-term researches of interspecific hybrids of wheat, it is offered to include in species of Triticum only seven species: T.boeticum, T.urartu T.araraticum, T.dicoccoides, T.timopheevi, T.dicoccum, T.spelta. All other species concern to natural cultural ecology-geographical categories - species and subspecies of wheat.
Keywords: Taxonomic traits